Netizens' Communication Ethics on Instagram in Islamic Perspective - Dianto, Icol; Nasution, Leli Asyuro; Rafiq, Mohd (Communicator: Journal of Communication, 2025)
Communication ethics are important, but many Instagram media users ignore them in the digital age. This study analyzes the message between content creators and followers, the reasons netizens comment, and the importance of maintaining Islamic communication ethics in commenting on Instagram. Using a qualitative approach with interactive analysis (Miles and Huberman), data were collected through observation and interviews with followers. The study results show that communication between content creators and followers involves exchanging messages through content such as videos and photos. Many negative comments arise due to dissatisfaction with the expression of content, but some netizens give positive views because of the motivation in learning the recitation. This study emphasizes the importance of six Islamic communication principles (qawlan sadidan, qawlan baligha, qawlan ma'rufa, qawlan kariman, qawlan layyina, qawlan maysura) to maintain communication ethics and harmonious relationships on social media.